Performance-Oriented Mobility Assessment test and Timed Up and Go test as predictors of falls in the elderly - A cross-sectional study - Sakthivadivel, Varatharajan; Geetha, Jeganathan; Gaur, Archana; Kaliappan, Ariyanachi (Journal of family medicine and primary care, 2022)
ABSTRACT Background: Falls are common in the elderly and frequently have serious consequences, which lead to physical and psychological complications. Assessment of fall risk in the elderly is performed by using functional assessment tools that assess the muscle strength, balance, functional mobility, and gait. Timed Up and Go test (TUG) assesses functional mobility and the Performance-Oriented Mobility Assessment test (POMA) assesses balance, postural control, and gait. Aim: This study compares the TUG test and POMA test in fall prediction among elderly patients. Materials and Methods: Patients with acute illness, acute painful lower limb conditions, dementia, severe depression, and those who are not willing were excluded from the study. Patient demographic data, co-morbidities, habits, and risk factors such as a previous history of falls, arthritis, depression, and vision impairment were noted. Gait and balance were assessed by the TUG and POMA tests. TUG and POMA were compared with the patients with a history of falls. Results: The mean age of participants was 70.79 ± 5.38 years. The females (57.6%) were more than the males. Hypertension was the commonest co-morbidity (54.4%). Out of 340 subjects, 105 subjects had a history of falls. The sensitivity of the TUG and POMA tests was 76.2 and 69.5%, respectively, and the specificity was 91.1 and 89.8%, respectively. The Kappa values were 0.680 and 0.606, respectively. POMA (r = -0.372) was negatively correlated to falls and TUG (r = 0.642) was positively correlated to falls. Conclusion: TUG is a useful measure for determining the risk of falling in older persons.